2013
DOI: 10.7243/2052-434x-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Taming the tide of HIV and TTI scourge in Sub-Saharan Africa using autologous blood transfusion

Abstract: Background and objective: The re-emergence of Transfusion Transmissible Infections (TTIs) and Human Immunodeficiency Virus (HIV) through allogeneic blood transfusion has made the subject of autologous blood transfusion to begin to gain adequate attention globally in recent times. This study aimed at enlightening the public on the importance of Autologous blood transfusion as a strategy in curbing HIV, TTI and allogeneic blood transfusion reaction in sub-saharan Africa where poor screening of blood contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The patient with the highest number of blood transfusion received 25 units of blood within a duration of 3 months. However, in addition to blood transfusion that may be associated with transmissible diseases, 29 erythropoietin was also used to correct the anemia in those patients who could afford it. Three of the patients with severe anemia refused blood transfusion on account of their faith and were treated with rhEPO for the anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The patient with the highest number of blood transfusion received 25 units of blood within a duration of 3 months. However, in addition to blood transfusion that may be associated with transmissible diseases, 29 erythropoietin was also used to correct the anemia in those patients who could afford it. Three of the patients with severe anemia refused blood transfusion on account of their faith and were treated with rhEPO for the anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Any of these could account for the low seroprevalence of the above transfusion transmissible infections encountered in our study. There is need to scaleup the screening processes of blood in our regional blood banks to antigen-based method [27]. Similarly, the mode of selection of our prospective blood donors must be addressed as majority of them, if not all, are commercial (remunerated/ paid) donors.…”
Section: Conclusion/recommendationsmentioning
confidence: 99%
“…Again, this was not unexpected as hepatitis B virus is a transfusion transmissible infectious agent. Previous studies have shown unsafe blood transfusion practice as one of the modes of transmission of HBV infection especially in resource-limited centers of sub-Saharan Africa where the standard of screening is poor and commercial (remunerated) blood donation constitute major source of blood supply in the national blood transfusion centers [36,40]. The odd ratio (OR) of previous blood transfusion from this study was 5.2.…”
Section: Sero-epidemiology Of Hbsag Among Health Workers In a South-ementioning
confidence: 68%